The detection of DNA damage response in MCF7 and MDA-MB-231 breast cancer cell lines after X-ray exposure - Mahmoud, Alkhansa; Casciati, Arianna; Abu Bakar, Zuki; Hamzah, Hazilawati; Tengku Ahmad, Tengku Ahbrizal Farizal; Mohd Noor, Mohd Hezmee (ScienceOpen, 2023)
Radiotherapy is one of the main options to cure and control breast cancer. The aim of this study was to investigate the sensitivity of two human breast cancer cell lines, MCF7 and MDA-MD-231, to radiation exposure at timepoints 4 h and 24 h after radiation. MCF7 and MDA-MD-231 were irradiated with different radiation doses using a Gilardoni CHF 320 G X-ray generator (Mandello del Lario, Italy) at 250 kVp, 15 mA [with half-value layer (HVL) = 1.6 mm copper]. The ApoTox-Glo triplex assay combines three assays used to assess viability, cytotoxicity, and apoptosis. The expression of γH2AX and BAX was analyzed by Western blotting. Viability and cytotoxicity did not change 4 h and 24 h after irradiation in either cell line, but we found a significant increase in the expression of cleaved caspase-3/7 at 24 h after irradiation with 8.5 Gy in MDA-MB231. The expression of γH2AX and BAX was low in MCF7, whereas the expression of γH2AX and BAX increased with radiation dose in a dose-dependent manner in MDA-MB231. The results show that the MCF7 cell line is more radioresistant than the MDA-MB 231 cell line at 4 h and 24 h after X-ray irradiation. In contrast, MDA-MB-231 cells were radiosensitive at a high radiation dose of 8.5 Gy at 24 h after irradiation. γH2AX and BAX indicated the radiosensitivity in both cell lines. These results open the possibility of using these cancer cell lines as models for testing new therapeutic strategies to improve radiation therapy.